HUBUNGAN TINGKAT PENGETAHUAN TENTANG TRIAGE DENGAN SIKAP PERAWAT PADA PASIEN TRIAGE PRORITAS 1 DAN 2 DI INTALANSI GAWAT DARURAT RSUD TANJUNG KABUPATEN LOMBOK UTARA - Ni Made Sumartyawati; Ade Rizki Prayuda; Antoni Eka Fajar Maulana; I Made Eka Santosa (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: The high number of visits to the Emergency Room by patients with urgent and non-urgent conditions is the main cause of overcrowding in the Emergency Room. The knowledge and experience of triage nurses are important factors in making triage decisions in most hospitals. Objective: to determine the relationship between the level of nurse knowledge and the attitude of nurses towards priority patients 1 and 2 in the Emergency Room Method: This study is a descriptive correlational study, with a cross-sectional approach. The sampling technique is total sampling with a sample size of 19 nurses. Result: Knowledge variable 11 respondents at a good level of knowledge, 4 respondents at a sufficient level of knowledge, and 4 respondents at a poor level of knowledge. The attitude variable in the appropriate category is 16 respondents and the inappropriate category is 3 respondents. The results of the Spearmank rank test p - value of 0.033 because the sig. (2-tiled) value of 0.033 is smaller than <0.005. Conclusion: there is a relationship between the level of knowledge about triage and the attitude of nurses towards priority patients 1 and 2 in the Emergency Room.